2018
DOI: 10.1002/fsn3.584
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the antioxidant and intestinal protective effects of extracts from different parts of Java tea (Orthosiphon stamineus)

Abstract: The aim of this study was to compare the free radical scavenging ability and intestinal epithelial cell protective effects of Java tea (Orthosiphon stamineus) root extracts (ORE), stem extracts (OSE), and leaf extracts (OLE) to determine the potential of Java tea by‐products. The Java tea extracts were prepared using a standard water–ethanol method. The antioxidant activity and intestinal protective effects were tested by H2O2‐induced cell model and high‐fat diet‐induced mice model, respectively. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
4
28
0
8
Order By: Relevance
“…anthocyanins and proanthocyanidins and their biosynthesis is usually higher in berries than is (Giada et al, 2013). Based on the available literature (Zengin et al, 2015;Mena et al, 2018;Mollica et al, 2018;Cai et al, 2018), the chemical and biological approaches on different…”
Section: Polyphenolics Profilementioning
confidence: 99%
“…anthocyanins and proanthocyanidins and their biosynthesis is usually higher in berries than is (Giada et al, 2013). Based on the available literature (Zengin et al, 2015;Mena et al, 2018;Mollica et al, 2018;Cai et al, 2018), the chemical and biological approaches on different…”
Section: Polyphenolics Profilementioning
confidence: 99%
“…We previously showed that OE protected the intestine against oxidative stress [6]. However, there are no reports confirming that RA is the predominant effective compound in the antioxidant activity of OE.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CSH was used as one of the predominant ingredients in “Xueniao'an granules,” which was a very popular traditional Chinese medicine prescription for the treatment of urolithiasis. Pharmacological studies have shown that CSH has antimicrobial, antioxidant, hepatoprotective, antigenotoxic, antiplasmodial, cytotoxic, cardioactive, antidiabetic and anti‐inflammatory activities . Polymeric phenolic acids, flavonoids, diterpenes, triterpenes, essential oils and polysaccharides have been isolated from CSH by phytochemical approaches .…”
Section: Introductionmentioning
confidence: 99%
“…shown that CSH has antimicrobial, antioxidant, hepatoprotective, antigenotoxic, antiplasmodial, cytotoxic, cardioactive, antidiabetic and anti-inflammatory activities. [2][3][4][5][6] Polymeric phenolic acids, flavonoids, diterpenes, triterpenes, essential oils and polysaccharides have been isolated from CSH by phytochemical approaches. [7][8][9][10][11] Published literature concerning CSH has mainly focused on the quantification of several phenolic acids or flavonoids by high-performance liquid chromatography-photodiode array detector method or high-performance liquid chromatography/ tandem mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%